Representasi Pariwisata Budaya Madura dalam Puisi Sastrawan Madura dan Relevansinya sebagai Materi Pembelajaran Sastra di Era Merdeka Belajar - Rahman, Syaiful (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2022)
Literature is a replica of life and culture. Therefore, literary learning should be directed in a more creative, innovative, free and fun way, so that students will not be bored and the noble values ​​in literature can be felt directly by students. The purpose of this study is to describe Madura cultural tourism contained in the poetry of Madurese writers and their relevance as literary learning materials in the era of independent learning. The method used in this study is a qualitative descriptive method with a tourism literary theory approach. Data and data sources, the data are in the form of sentence excerpts that represent Madura cultural tourism, while the data sources for this research come from a collection of poetry by Madurese writers. The instrument used for data collection in this study was the researcher himself. The data collection technique in this study was carried out by the note-taking method. To analyze the data, the researcher used the Milles & Huberman model by modifying it as needed. The results showed that there were 14 books of poetry collections of Madurese writers with the theme of Madura cultural tourism, consisting of 69 poetry titles, 121 data were found, with details of 105 data representing Madura traditional tourism and 16 data representing Madura art tourism. Poems written by Madurese writers are relevant if they are used as material for literary learning in the era of independent learning.